Lateral Lumbar Interbody Fusion: Single Surgeon Learning Curve - Jacob, Kevin C.; Patel, Madhav R.; Prabhu, Michael C.; Vanjani, Nisheka N.; Pawlowski, Hanna; Munim, Mohammed A.; Singh, Kern (World neurosurgery, 2022)
To characterize lateral lumbar interbody fusion surgical learning curve and investigate changes in perioperative and postoperative clinical parameters associated with increased operative experience. In a case series, surgical learning curve was defined using 3-parameter asymptotic regression and piecewise linear regression, yielding learning phase (patients 1–53) and proficient phase (patients 54–179) cohorts. Using a 5-point grading scale, ipsilateral iliopsoas (hip-flexion) and quadriceps (knee-extension) muscle strength and thigh and groin sensory disturbances were compared for differences preoperatively versus postoperatively using χ2 test. Patient-reported outcome measures were collected preoperatively and postoperatively and compared between cohorts with unpaired t test. The proficient phase cohort demonstrated significantly reduced operative time, estimated blood loss, postoperative length of stay, and narcotic consumption on postoperative days 0 and 1. The proficient phase cohort displayed decreased disability at 6 weeks and 6 months and demonstrated significant improvement at all time points for disability, pain, and physical function except for 6 weeks and 2 years for physical function, whereas the learning phase cohort demonstrated improvement in disability beginning at 6 months, leg pain at all time points, and back pain through 6 months. Ipsilateral groin and thigh sensory disturbances and iliopsoas and quadriceps weakness improved with increasing operative experience. The proficient phase cohort demonstrated significantly improved perioperative profile, reduced complication rate, and reduced rates of iliopsoas and quadriceps weakness. While the proficient phase cohort demonstrated earlier improvement in disability and physical function scores compared with the learning phase cohort, 2-year outcome measures did not differ. Long-term clinical outcomes suggest that patient safety and quality of life are not compromised during the learning phase, but patients may be particularly susceptible to femoral nerve injury early in a surgeon’s practice.